133k views
2 votes
Please help will give you a 5 star rating

Please help will give you a 5 star rating-example-1
User Nxlevel
by
4.5k points

2 Answers

3 votes

Answer:

Slope I think its says, so: 3

Explanation:

Take

6 = y2 , 0 = y1 , 0 = x2 , -2 = x1

y2 - y1 over x2 - x1

6-0

0+2 (because 2 is negative)

=

6/2

which reduced makes 3!

Hope this helps, and have a good day.

And for the 0 + 2:

its

0 - ( - 2 )

- ( - makes a big plus so add :)

User Scoates
by
4.6k points
4 votes

Answer:

3

Explanation:

To find the average rate of change

f(0) - f(-2)

-----------------

0 - -2

Taking the values for f(0) = 6 and f(-2) =0

6 - 0

---------

0+2

6/2

3

User Reznic
by
4.7k points